1997
DOI: 10.1093/oxfordjournals.eurheartj.a015225
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo-controlled study of the effects of simvastatin on haemostatic variables, lipoproteins and free fatty acids

Abstract: The Oxford Cholesterol Study is a randomized placebo-controlled trial designed primarily to assess the effects of simvastatin on blood cholesterol levels and side-effects in preparation for a large, long-term trial of the effects of cholesterol-lowering drug therapy on mortality. At present there is only limited evidence from randomized comparisons of the effects of HMG-CoA reductase inhibitors, such as simvastatin, on thrombogenic, as distinct from atherogenic, pathways in coronary heart disease. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…The Oxford Cholesterol Study Group analyzed the effect of simvastatin on a number of hemostatic variables including PAI-1. Simvastatin, which has clearly demonstrated a decreased incidence of cardiovascular event rates in large-scale trials, was correlated with a decrease in factor VII antigen levels but had no significant effect on fibrinogen [33]. Plasminogen activator inhibitor activity was increased in patients who received simvastatin and no significant alteration in other hemostatic variables were attained in this small study of 162 participants who were subdivided into three groups.…”
Section: Coagulationmentioning
confidence: 58%
“…The Oxford Cholesterol Study Group analyzed the effect of simvastatin on a number of hemostatic variables including PAI-1. Simvastatin, which has clearly demonstrated a decreased incidence of cardiovascular event rates in large-scale trials, was correlated with a decrease in factor VII antigen levels but had no significant effect on fibrinogen [33]. Plasminogen activator inhibitor activity was increased in patients who received simvastatin and no significant alteration in other hemostatic variables were attained in this small study of 162 participants who were subdivided into three groups.…”
Section: Coagulationmentioning
confidence: 58%
“…strated an increase in PAI-1 activity, whereas pravastatin treatment was associated with a decrease in PAI-1 (20,42,43). A recent study using SV40-transformed rat aortic endothelial cells demonstrated a decrease in PAI-1 activity in response to lovastatin (44).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced fibrinolytic capacity is mainly caused by elevated plasminogen activator inhibitor activity, the principal inhibitor of the fibrinolytic system, and to a lesser extent by Lp(a). Lovastatin and pravastatin lower PAI-1 levels [66][67][68], whereas simvastatin either elevates or does not change PAI-1 [70].…”
Section: Thrombosismentioning
confidence: 91%